2010
DOI: 10.3354/meps08842
|View full text |Cite
|
Sign up to set email alerts
|

Physical forcing of distributions of bryozoan cyphonautes larvae in a coastal embayment

Abstract: In shallow rocky subtidal ecosystems in the western North Atlantic, outbreaks of the nonindigenous encrusting epiphytic bryozoan Membranipora membranacea cause defoliation of laminarian algae, facilitating a phase transition from native kelp beds to meadows of invasive algae. We quantified spatial (m [depth] to km [sites]) and temporal (hourly to monthly) patterns in the abundance of larvae of M. membranacea, and a morphologically similar native species, Electra pilosa, in relation to physical structure (tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
3
2
Order By: Relevance
“…For bryozoans (cyphonautes), tidal height was the factor that best explained their abundance patterns. Saunders & Metaxas (2010) suggested that onshore transport of cyphonautes occurs during wind-driven downwelling events; however, in our study we did not have any such events. Differences found in the delivery mechanism between studies may be related to regional variability in the vertical distribution of larvae.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…For bryozoans (cyphonautes), tidal height was the factor that best explained their abundance patterns. Saunders & Metaxas (2010) suggested that onshore transport of cyphonautes occurs during wind-driven downwelling events; however, in our study we did not have any such events. Differences found in the delivery mechanism between studies may be related to regional variability in the vertical distribution of larvae.…”
Section: Discussioncontrasting
confidence: 57%
“…Differences found in the delivery mechanism between studies may be related to regional variability in the vertical distribution of larvae. For example, Saunders & Metaxas (2010) found higher abundances of cyphonautes closer to the surface in Nova Scotia, whereas in California, near our study site, other authors (Bernstein & Jung 1979, Yoshioka 1982, Pineda 1999 found that they occurred below the thermocline in strongly stratified Table 2. Models representing hypotheses of onshore larval transport at San Miguel beach.…”
Section: Discussioncontrasting
confidence: 47%
“…Also, the obligate dispersal of feeding cyphonautes larvae before metamorphic competence might enlarge the area that progeny occupy, in contrast to the distribution of a brooder, Bugula neritina , in an eelgrass bed, which was limited by a short distance of larval dispersal (Keough & Chernoff, 1987). However, for two nonbrooders, Membranipora and Electra , the dispersal during feeding and growth of the cyphonautes larvae exceeded what was necessary for occupying a local habitat (Saunders & Metaxas, 2010).…”
Section: Brooding and Nonbrooding In Marine Benthic Coloniesmentioning
confidence: 99%
“…The highest concentrations of bryozoans occurred at 18 m, and showed a positive relationship with fluorescence (Lloyd et al 2012a). In contrast, bryozoan abundance in St. Margarets Bay (also in Nova Scotia) was higher at 4 m than at 12 m (Saunders & Metaxas 2010). However, the salinity and temperature at 4 m depth in St. Margarets Bay was more similar to that at 12 m in St. George's Bay.…”
Section: Discussionmentioning
confidence: 76%